The role of negativity bias in political judgment: A cultural neuroscience perspective - Pornpattananangkul, Narun (Behav Brain Sci, 2014)
Hibbing et al.this issue provide a comprehensive overview of how being susceptible to heightened sensitivity to threat may lead to conservative ideologies. Yet, an emerging literature in social and cultural neuroscience shows the importance of genetic and cultural factors on negativity biases. Promising avenues for future investigation may be examining the bidirectional relationship of conservatism across multiple levels of analysis.